2010
DOI: 10.1002/pssr.200903304
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of electroluminescence images of solar cells

Abstract: A fast converging iterative procedure is proposed to calculate series resistance (Rs) and saturation current (j0) images from two electroluminescence (EL) images taken at two biases. It is not necessary here that for one bias the influence of the series resistance is negligible. Moreover, voltage series of EL images have been evaluated for calculating images of Rs, j0, and the parallel conductance Gp separately. However, it has been found that Rs variations cannot uniquely be separated from Gp variations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…It is observed that the cells with DRE have diffusion length varying from 90 to 150 lm where as in cells with non-DRE the diffusion length vary from 25 to 95 lm. Since the diffusion length is directly proportional to the carrier lifetime we can conclude that improvement in lifetime of the carriers results in improved electrical performance of solar cells [11][12][13]. With increase in diffusion length in a device the generation life time increases as per the relation, L d ¼ ½lð kT q Þt g 1=2 [14], where, L d is the diffusion length and t g is the generation lifetime.…”
Section: Resultsmentioning
confidence: 94%
“…It is observed that the cells with DRE have diffusion length varying from 90 to 150 lm where as in cells with non-DRE the diffusion length vary from 25 to 95 lm. Since the diffusion length is directly proportional to the carrier lifetime we can conclude that improvement in lifetime of the carriers results in improved electrical performance of solar cells [11][12][13]. With increase in diffusion length in a device the generation life time increases as per the relation, L d ¼ ½lð kT q Þt g 1=2 [14], where, L d is the diffusion length and t g is the generation lifetime.…”
Section: Resultsmentioning
confidence: 94%
“…Five or more images can be used, while more images will reduce the residual noise. Compared to other publications [1,2,4,[6][7][8][9][10], additional maps of diode dark saturation current densities of a two diode model, current density, power density, fill factor and efficiency can all be calculated. Furthermore, no assumptions are used for the commonly needed local calibration constant.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several publications [1,2,4,[6][7][8][9][10] focused on the extraction of spatially resolved maps of electrical parameters from photoluminescence (PL) images. The majority of the methods [4,[6][7][8] require a local calibration constant C xy that is calculated in an individual step with its own PL images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One special application for the characterization of finished solar cells is the extraction of spatially resolved solar cell parameters from a series of images taken at different operating conditions. Up to now, methods have focused on the extraction of the local series resistance [3]- [5] and the local dark saturation current density [6]- [9]. These methods, however, assume a laterally homogeneous short-circuit current density, which corresponds to laterally homogenous external quantum efficiency.…”
Section: Introductionmentioning
confidence: 98%